Asset management decision making of power transformer with insulation ageing knowledge - Katim, Nurul Izzatul Akma (2013)
Transformer represents a substantial asset. Transformer’s ageing has recently become a great concern and challenge to all electric utilities around the world. Utilities today face the twin challenges of satisfying increasingly high standards for reliability and service quality while at the same time reducing costs and improving earnings. Asset management has been recognized as their framework for allocating capital and operation/maintenance budgets. The challenge is to align the business requirement and the scientific and technical knowledge of the assets in order to make business decisions. There are various management concepts, maintenance methodologies and asset technical evaluations that are currently exist and practiced in the industries. The focus of this project is to align transformer ageing knowledge to the business process of asset management. The methodology employed to produce the decision making process is through integration and application of existing knowledge in asset management with PAS 55 as a benchmark. As a result, an asset manager’s decision making process is proposed, which link the business requirement and technical knowledge of asset condition, using risk-based management. By linking these requirements, asset managers will be able to quantify risk, justify expenditures which will meet the technical requirement of asset condition and in line with the business plan